Menggali aktivitas bermain, status gizi dan motivasi belajar terhadap hasil belajar pada anak - Triani Aulia, Restia; Welis, Wilda; Neldi, Hendri; Sujana Wahyuri, Asep; Zarya, Fiky (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2024)
Children's learning outcomes are in the low category, based on play activities, nutrition and motivation owned by children. This study aims to reveal the play activities, nutrition, and motivation children possess. This research method is correlation using quantitative methodology through a path analysis approach. The population in the study was upper-grade elementary school students. This sampling technique is random sampling, randomly taking 50% of each class at public elementary school 8 Lubuklinggau, a total of 79 students. Data were collected using questionnaires for learning motivation, anthropometric tests to obtain students' nutritional status, and primary data used to see the learning outcomes obtained. The results show the relationship between the independent variable and the dependent variable, with the Beta coefficient having a value of 0.009 for X1 and X3 (p31) and 0.092 for X2 and X3 (p32). While the second structure shows the relationship between the independent variables X1Y, X2Y, and X3Y with the same dependent variable, with the Beta coefficients having values of 0.236 for X1Y (py1), 0.219 for X2Y (py2), and 0.313 for X3Y (py3), it can be concluded that there is a simultaneous influence of play activities, nutritional status and motivation on learning outcomes. In conclusion, research shows that nutritional status and learning motivation play an important role in shaping student learning outcomes at public elementary school 8 Lubuklingau, Padang, Indonesia, with nutritional status also indirectly affecting learning outcomes through its impact on learning motivation.